Eksperimen Pembelajaran Matematika Dengan Strategi Team Assisted Individualization Dan Quiz Team Ditinjau Dari Kemampuan Pemecahan Masalah Siswa Kelas VIIIDi SMP Muhammadiyah 8 Surakarta - Herlina Wati Putri, Rizki, Rita Pramujiyanti Khotimah,S.Si, M.Sc (2017)
This research aims to analyze and examine: (1) the influence of learning strategies Team Assisted Individualization (TAI) and Quiz Team against the results of the learning of mathematics, (2) the influence of students ' problem-solving ability against the results of the learning of mathematics, (3) the effect of the interaction between the learning strategies and problem-solving abilities students toward outcome studied mathematics. This research is quantitative research design with a quasi experiment. The population of this research are all students of class VIII JUNIOR Muhamadiyah Surakarta 8 school year 2016/2017. The sample in this study consists of two classes, namely as a class experiment and the control class with sampling techniques using cluster random sampling. Data collection techniques used are tests and documentation. Data analysis techniques using variansi analysis of two streets with cells not equal to 5% significance level. Based on the analysis of the obtained conclusions that: (1) there is the influence of learning strategies Team Assisted Individualization (TAI) and Quiz Team against the results of the learning of mathematics, (2) there is the influence of the students ' problem-solving ability against the results of the learning of mathematics, (3) there is no effect of the interaction between the learning strategy Team Assisted Individualization (TAI) and Quiz Team in terms of problem-solving ability against the results of the learning of mathematics. Keywords: problem-solving ability, Quiz Team, results of learning math, Team Assisted Individualization